Application of discrete element method (DEM) in characterization of bond-slip behavior in RC beams with confinement subjected to corrosion. (December 2020) - Yazarlu, Abbas; Dehestani, Mehdi
Abstract: In this study, the application of the discrete element method (DEM) for characterization of bonding behavior at the rebar/concrete interface of reinforced concrete (RC) beams subjected to different levels of corrosion is investigated. For this purpose, a set of experimental under-reinforced and balanced-reinforced concrete beams are selected from the literature, which were subjected to chloride-induced corrosion for different periods. The DEM defines the bond between rebar and concrete by three key contact parameters including friction coefficient, contact pressure, and clearance. A set of contact parameters that yields the minimum integral absolute error (IAE) is selected as the optimum. In an attempt to increase the accuracy of the optimization process, an artificial neural network (ANN) model is used to fill the gaps between the values considered in the parametric study. Based on the analysis results, the DEM can predict the force-deflection curve of corroded under-reinforced beams with high accuracy both in the pre- and post-cracking branches. However, in balanced-reinforced beams, the numerical curve deviates from the experimental one in the post-cracking branch. Furthermore, the use of ANN model can reduce the IAE by up to 40%, which indicates the effectiveness of the model in reducing the error in numerical simulations. In addition, the results show that the friction coefficient is more critical in DEM than other contact parameters.